Early, late or never? When does parental education impact child outcomes? - Matt Dickson; Paul Gregg; Harriet Robinson (Institute for the Study of Labor (IZA), 2013)
We study the intergenerational effects of parents' education on their children's educational outcomes. The endogeneity of parental education is addressed by exploiting the exogenous shift in education levels induced by the 1972 Raising of the School Leaving Age (RoSLA) from age 15 to 16 in England and Wales. Using data from the Avon Longitudinal Study of Parents and Children - a rich cohort dataset of children born in the early 1990s in Avon, England - allows us to examine the timing of impacts throughout the child's life, from pre-school assessments through the school years to the final exams at the end of the compulsory schooling period. We also determine whether there are differential effects for literacy and numeracy. We find that increasing parental education has a positive causal effect on children's outcomes that is evident at age 4 and continues to be visible up to and including the high stakes exams taken at age 16. Children of parents affected by the reform gain results approximately 0.1 standard deviations higher than those whose parents were not impacted. The effect is focused on the lower educated parents where we would expect there to be more of an impact: children of these parents gaining results approximately 0.2 standard deviations higher. The effects appear to be broadly equal across numeracy and literacy test scores.
Keywords: I20; J62; J24; 330; intergenerational mobility; schooling; child development; Kinder; Bildungsniveau; Eltern; Generationenbeziehungen; Großbritannien